A wager to tempt the runaway - Scott, Bronwyn, 1967- (Scott, Bronwyn, 1967- Rebellious sisterhood., 2021)
"Josefina Ricci has run away to fulfill her deathbed promise to her father to travel the world! During her stop in England, the free-spirited artist is embroiled in a wager--to paint an award-winning portrait of oyster businessman Owen Gann in exchange for room and board. Owen is her opposite in all ways, pragmatic and responsible, but as he reveals a wild, passionate side, might Josefina have found her greatest adventure...in him?"--